Specification for bitumen road emulsions ( anionic and cationic ) Part 1. Requirements - British Standards Institution (London BSI, 1973)
Bitumens, Roads, Construction materials, Anions, Cations, Wearing courses (roads), Emulsions, Pavements (roads), Composition, Marking, Life (durability), Stability, Viscosity measurement, Sampling methods, Sieving, Water content determination, Binding agents, Test equipment, Viscometers, Coagulation, Sedimentation
Superseded, Withdrawn
Replaced by BS 434-1:1984
Keywords: Bituminous products -- Standards